1998
DOI: 10.1063/1.366640
|View full text |Cite
|
Sign up to set email alerts
|

Cd self-doping of CdTe polycrystalline films by co-sputtering of CdTe–Cd targets

Abstract: Cadmium self-doped CdTe polycrystalline films were grown on Corning glass substrates at room temperature by cosputtering from a CdTe-Cd target. The electrical, structural, and optical properties of the films were analyzed as a function of the Cd concentration. Films with a stoichiometric composition, and slightly below and above it, were prepared. In films where the Te exceeds 50 at. %, it is found segregation of Te and its electrical resistivity is about 10 7 ⍀ cm. In those with an excess of Cd, the electrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…All spectra showed the CdTe longitudinal optical (LO) mode at the frequency of 166.5 cm −1 and their second order (2LO) mode at 333 cm −1 , characteristic of CdTe. 6 The LO modes of cubic and hexagonal phases of CdTe can coincide at the same frequency, 13 so these measurements agree with those of XRD. The features located at 123 and 142 cm −1 correspond to the phonon vibrations A 1 and E 1 modes, respectively, in the hexagonal Te structure.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…All spectra showed the CdTe longitudinal optical (LO) mode at the frequency of 166.5 cm −1 and their second order (2LO) mode at 333 cm −1 , characteristic of CdTe. 6 The LO modes of cubic and hexagonal phases of CdTe can coincide at the same frequency, 13 so these measurements agree with those of XRD. The features located at 123 and 142 cm −1 correspond to the phonon vibrations A 1 and E 1 modes, respectively, in the hexagonal Te structure.…”
Section: Resultssupporting
confidence: 78%
“…The features located at 123 and 142 cm −1 correspond to the phonon vibrations A 1 and E 1 modes, respectively, in the hexagonal Te structure. 6,14 The Te characteristic signals appears well defined in 2a) and 2c) spectra and weaker but still noticeable in 2b) spectrum. The Raman measurements indicate that undoped and Cu-doped CdTe films grew with an excess of Te.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The Raman spectra were recorded in backscattering geometry at room temperature, using either a 64000 Jovin Yvon spectrometer with the 515 nm argon laser line or a Bruker RFS 100/S spectrometer with the 1064 nm Nd:YAG laser line. The power densities were at least ~10 3 In (c) previous to recording the spectra the sample was exposed to the same radiation for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Shin et al [1] have attributed them to Te precipitates present as a part of growth process of CdTe. Picos-Vega et al [3] studied CdTe samples grown either with Cd or Te excess and observed in Te rich material Te related optical modes at 123 cm -1 and 142 cm -1 , whereas in Cd rich material modes at 167 cm -1 and 334 cm -1 were measured. The authors concluded that the Te modes were due to small Te aggregates related with poor stoichiometry and disappeared gradually with the increase of cadmium content.…”
Section: Introductionmentioning
confidence: 98%